From Demons to Droids: A Comparative Study of Supernatural and AI Horror in Global Cinema - Jannatul Ferdous Himika; Sk. Sabbir Ahmed (CV Projurnal Mitra Publikasi, 2025)
Horror cinema has continually evolved to mirror society’s prevailing fears, shifting from supernatural narratives rooted in folklore and religion to technologically driven anxieties surrounding artificial intelligence. This study presents a comparative analysis of supernatural and AI horror by examining their narrative structures, visual aesthetics, audience responses, and theoretical underpinnings. Drawing on Noël Carroll’s concept of the supernatural as a violation of the natural order and Baudrillard’s notion of simulated realities, the research investigates films such as Annabelle, M3GAN, Tatya Vinchu (India), and Putuler Protishodh (Bangladesh) Supernatural horror often relies on chaotic, demonic forces and spiritual themes, resonating strongly in cultures with deep-rooted beliefs in the paranormal. In contrast, AI horror introduces humanlike yet emotionally detached antagonists, exemplified by the Uncanny Valley effect, which heightens unease through artificial realism. Findings reveal that while AI horror is gaining global prominence with the rise of digital technologies, supernatural horror retains its cultural significance, especially in regions where spiritual beliefs prevail. The study concludes that horror cinema remains a powerful lens through which societal anxieties are explored, continually adapting to reflect fears both ancient and modern.